Circadian feeding rhythm of green-belly stink bug in corn cultivation - Castilhos, Rodolfo Vargas; Ribeiro, Leandro do Prado; Carvalho, Gabriel de (Pesquisa Agropecuaria Brasileira, 2020)
The objective of this work was to evaluate the circadian feeding rhythm of the green-belly stink bug (Dichelops melacanthus) on corn (Zea mays), and to correlate it with meteorological parameters. The experiments were conducted in corn fields in the first (summer) and second (fall) crop seasons, in the municipality of Chapecó, in the state of Santa Catarina, Brazil. Plants in the V3 and V5 stages were covered with cages and infested with adults of D. melacanthus. After 24 hours of acclimation, the number of insects feeding on the plant stem was counted every three hours (at 6:00, 9:00, 12:00, 15:00, 18:00, 21:00, and 0:00 h). At night, a red led flashlight was used to visualize the insects without interfering with their behavior. Meteorological parameters were monitored and correlated to the number of insects feeding on the plants. In the first and second crop seasons, the number of insects feeding on the corn stem differed among evaluation times, with peak in the afternoon, in the evening, and at night. Few insects were found feeding at 6:00 and 9:00 h. There was a positive correlation between air temperature and feeding in both seasons. In milder temperature regions, the preferred feeding time of D. melacanthus on corn is during the afternoon, evening, and night hours, which should be taken into account for a precise management of this insect.